2020
DOI: 10.1071/ah18252
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of Australia's GP workforce: estimating supply and demand, 2005–06 to 2015–16

Abstract: Objective A 2011 Australian study calculated average annual general practitioner (GP) utilisation and predicted numbers required to meet demand to 2020. The objective of the present study is to calculate average annual GP utilisation in 2015–16 compared with clinical demand predicted in 2005–06. Methods Demand was calculated from Medicare Benefits Schedule, Department of Veterans’ Affairs and Australian Bureau of Statistics data. Length of consultation and average clinical hours worked per week (from 2002–03 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Moreover, one study showed that burnout had a direct effect on GPs' turnover intention (Zhang et al 2021). Similar to the UK, the Australian PHC workforce has been under a significant amount of pressure for some time, with the ever-expanding workload due to GP shortage, (The Guardian 2021) and the growing aging population (Dingwall et al 2020). Crisis events, such as the pandemic, further exacerbate the problem; for example, the UK is currently facing a potential exodus of GPs due to a 'burnout workforce' (The Guardian 2021).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Moreover, one study showed that burnout had a direct effect on GPs' turnover intention (Zhang et al 2021). Similar to the UK, the Australian PHC workforce has been under a significant amount of pressure for some time, with the ever-expanding workload due to GP shortage, (The Guardian 2021) and the growing aging population (Dingwall et al 2020). Crisis events, such as the pandemic, further exacerbate the problem; for example, the UK is currently facing a potential exodus of GPs due to a 'burnout workforce' (The Guardian 2021).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Planning for an adequate primary care workforce that is responsive to the changing needs of the Australian population will require an understanding of the practice patterns of GPs. 6 A focus on early-career GPs can provide relevant information on the working trends of recent fellows. Further cohort studies that follow early-career GPs over time, along with qualitative research components, are warranted to develop a deeper understanding of these trends.…”
Section: Implications For Policy and Further Researchmentioning
confidence: 99%
“…3 Although many GPs are satisfied with their job, 4,5 these demographic and societal changes are affecting their participation in clinical practice. The average number of clinical hours worked by GPs has decreased in recent years, 6 with the trend evident across career stages and genders. 7,8 Although female GPs work, on average, fewer hours than male GPs, 8 male GPs have also been reducing their clinical working hours.…”
mentioning
confidence: 99%
“…Further, uncertainty regarding the efficacy of exercise (recent Cochrane review published after the National survey) [49] may also impact on GPs decision making when managing RCRP. Finally, Australia has a maldistributed GP workforce [50] and a rapidly increasing population attendance rate to general practice [51], so it is possible that GPs lack the time to adequately assess and manage RCRP within their primary care setting [31,47].…”
Section: Gp Management Of Rcrpmentioning
confidence: 99%